Innovations of the Past: 70 Years of Polish Historiography - Pestrykov, Oleksandr (Acta Poloniae Historica, 2024)
On 22–24 November 2023, the Tadeusz Manteuffel Institute of History of the Polish Academy of Sciences hosted the conference ‘Innowacje przeszłości: 70 lat historiografi i polskiej’ [Innovations of the Past: 70 Years of Polish Historiography], both in person and virtually. The three-day event featured nine sessions, over 20 papers, and a panel discussion on social history. In celebration of the Institute’s 70th anniversary, the organisers aimed to explore the development of historiography in post-war Poland through the lens of innovation. The rather intriguing and paradoxical name of the academic event, which at fi rst sight combined the seemingly contradictory concepts of ‘past’ and ‘innovation’, proved highly pertinent and refl ected the spirit in which most of the participants conducted their deliberations. It also refl ected the point of view of the participants, which was to perceive the nature of historiography as quite dynamic and open: it is not only loyalty to tradition but also admiration for new trends and the desire for innovation that have characterised the development of Polish historiography over the past 70 years.